Ruthenium (II) polypyridyl complexes as photoprobes for DNA mismatches - PAUL TILEY (2022)
[Ru(bpy)2dppz]2+ is a classic “light switch” effect complex with a brighter emission for mismatched DNA than well-matched DNA. It is, therefore, a photoprobe for DNA. To enhance its selectivity for mismatched base pairs which can lead to DNA mutations, a range of related complexes were synthesized and investigated. The approach involved increasing the steric bulk of the ancillary 2,2’-bipyridine (bpy) ligands and/or the dipyridophenazine (dppz) functional group ligand. This functional group ligand is known to insert or intercalate between adjacent base pairs in the base stack of DNA and an alternative functional group ligand was also explored: 12,17-dihydronaphthodipyridophenazine-12,17-dione (aqphen). Hairpin and 12 base oligonucleotide duplex DNA containing mismatched base pairs were tested and compared to the same sequences containing well-matched base pairs. Methylation of the ancillary bpy ligands only at positions 5,5’ with dppz as the functional group ligand is highly selective for both the CC and the TT mismatches. For the former the signal is between 4 and 6.3x higher than it is for well-matched DNA and for the latter a 6x increase was recorded. It almost certainly binds to the DNA via intercalation and its performance in these experiments have identified a useful photoprobe for the identification of these mismatched base pairings. Methylation of the dppz functional group ligand at positions 10 and 12 produced large increases in emission intensity compared to the parent compound [Ru(bpy)2dppz]2+ but did not substantially increase the mismatch base pair selectivity. The use of aqphen instead of dppz as the functional group ligand increased the binding strength with DNA and, notably, it showed a higher binding affinity for a 12mer duplex containing a CC mismatched base pair versus the well-matched sequence; its mode of binding is likely to be intercalation. In summary, enhancing steric bulk through methylation of the ancillary bpy ligands has achieved the desired selectivity whilst the same modification to the inserting dppz functional group ligand has led to large increases in signal intensity without an improvement in selectivity. The use of aqphen as the functional group ligand, which also has a greater steric bulk compared to dppz, increased binding affinity as well as selectivity.